Crystal structure of N, N′-bis(salicylidene)-1,10-decanediamine, C10H20(NCHC6H4OH)2 - Yu Y.-Y. (Zeitschrift für Kristallographie - New Crystal Structures, 2006)
C24H32N2O2, monoclinic, C12/c1 (no. 15), a = 46.409(9) Å, b = 4.800(1) Å, c = 9.987(2) Å, β = 98.10(3)°, V = 2202.4 Å3, Z = 4, Rgt(F) = 0.047, wRref(F2) = 0.142, T = 296 K.